D´Antonio, Débora (2016) La prisión en los años 70. Historia, género y política. Buenos Aires: Editorial Biblos, 302 pp. - Grammático, Karin (Zona Franca, 2018)
D´Antonio, Débora (2016) La prisión en los años 70. Historia, género y política. Buenos Aires: Editorial Biblos, 302 pp.